الخبر في البلاغة العربية - Didin Faqihudin (Hunafa: Jurnal Studia Islamika, 2009)
The science of ma’ânî is a set of rules and of principles  employed to know how to make an Arabic sentence structure agreeing with  language situation and condition. One of the objects of the science of ma’ânî is  khabar. Khabar is  a sentence that  may be either true or false, depending on the reality. If the reality agrees with khabar, then  it is called true khabar, but if not, it is called false khabar. There are two purposes of delivering khabar, namely fâ’idat al-khabar and lâzim al-fâ’idah. Sometimes the purposes of khabar deviate from that two original purposes to become istirhâm, izhâr al-da’f, izhâr al-tahassur, etc.Kata Kunci: al-balâghah al-‘arabiyyah, ‘ilm al-ma’ânî, al-khabar